Community effectiveness of indoor spraying as a dengue vector control method: a systematic review - Samuel, Moody; Horstick, Olaf (PLoS neglected tropical diseases, 2017)
Author summary The effectiveness of indoor residual spraying (IRS) and indoor space spraying (ISS) as dengue vector control methods depends on many factors. This study aims to systematically review the evidence on the community effectiveness of indoor spraying of insecticides to reduce Aedes mosquito populations and thereby to control dengue transmission. A systematic literature review was performed in PubMed, EMBASE, LILACS, Web of Science, WHO library database (WHOLIS), Cochrane, and Google Scholar, including a manual search of the reference lists of the identified studies since its inceptions until 15.02.2017. A total of 39 articles were retrieved for full assessment. Seven studies were included and analysed after final application of inclusion and exclusion criteria: two IRS studies with control, one without, three ISS studies and one, respectively. One IRS study and four ISS studies showed good evidence of effectiveness on adult Aedes mosquitoes. Evidence of effectiveness of IRS as a larvicidal intervention exists but is still inadequate, and is weak for ISS. Evidence of effectiveness of IRS on human dengue cases as a single intervention exists, but was limited and not available for ISS. It is recommended to scale up the research regarding the community effectiveness of IRS and ISS, including measuring dengue transmission, particularly, for IRS with its residual effect. It is also suggested to study in depth the factors that could affect the community effectiveness of IRS and ISS on Aedes populations and on human dengue cases.
Gesehen am 04.01.2018